Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1128/jb.179.17.5582-5584.1997
|View full text |Cite
|
Sign up to set email alerts
|

Division pattern of a round mutant of Escherichia coli

Abstract: A round mutant of Escherichia coli, when grown in Methocel medium, forms chains of cells and does not form tetrads. This implies that successive division planes of the round mutant are parallel rather than perpendicular. These results differ from a previous proposal that division planes in this round mutant are perpendicular to the prior division plane (W. D. Donachie, S. Addinall, and K. Begg, Bioessays 17:569-576, 1995).When round mutants were originally isolated, they were conditional (temperature-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…However, the concept runs directly into conflict with the fact that spheroid E. coli cells, like those of some gram-negative cocci (58) and many gram-positive spheroid bacteria, e.g., S. aureus (19,54,61), are able to alternate the division plane. Indeed, this biological fact implies that after each division, the cell either has to change the entire pattern of murein assembly (9) or produce progeny with two or three different types of murein architecture within one cell. The "segregated sectors" on the murein surface of dividing spheroid E. coli cells were recently discovered (11), and the question of whether such sectors of one cell really do possess a different architecture arises.…”
Section: Vol 185 2003mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the concept runs directly into conflict with the fact that spheroid E. coli cells, like those of some gram-negative cocci (58) and many gram-positive spheroid bacteria, e.g., S. aureus (19,54,61), are able to alternate the division plane. Indeed, this biological fact implies that after each division, the cell either has to change the entire pattern of murein assembly (9) or produce progeny with two or three different types of murein architecture within one cell. The "segregated sectors" on the murein surface of dividing spheroid E. coli cells were recently discovered (11), and the question of whether such sectors of one cell really do possess a different architecture arises.…”
Section: Vol 185 2003mentioning
confidence: 99%
“…Generally, strands could run either parallel with or perpendicular to the plasma membrane to build up a planar network (regular or irregular) or a vertically oriented matrix, respectively. According to the predominant concept, glycan chains are arranged in parallel with the plasma membrane, are aligned in a head-to-tail manner, and are oriented perpendicularly to the cell axis (8,9,29). Taken together, these parameters define the regular murein network, which can be visualized as presented in Fig.…”
mentioning
confidence: 99%
“…It has been proposed that planes of successive divisions in spheroidal E. coli cells lie either parallel [29] or perpendicular [30] to each other, restricted to one or two dimensions, respectively. To test the hypothesis that divisions can occur in planes alternating in three dimensions [32], we have recently developed a method to generate spheriodal cells with secondary constrictions during growth in suspension [26].…”
Section: Resultsmentioning
confidence: 99%
“…The dispute about the relative planes of subsequent divisions in spheroidal E. coli [26,29,30] can be resolved by visualizing the nascent FtsZ rings [31] in such cells. This is the aim of the investigation described here.…”
Section: Introductionmentioning
confidence: 99%
“…The question whether this stems from a fundamental difference is moot. Cooper [1] presumes that the peptidoglycan 'constrained-hoop' structure of rod-shaped bacteria such as Escherichia coli forces them to divide in one dimension, while Begg and Donachie [2] demonstrated that they could do so in two. We have argued [3] that the rigid peptidoglycan forces the two replicating nucleoids to segregate along cell length and that division ring is placed at the envelope adjacent to and between them, irrespective of the previous location upon termination of a chromosome replication cycle [4].…”
Section: Introductionmentioning
confidence: 99%